2009
DOI: 10.1186/1479-5868-6-17
|View full text |Cite
|
Sign up to set email alerts
|

Disagreement in physical activity assessed by accelerometer and self-report in subgroups of age, gender, education and weight status

Abstract: Background: The purpose of this study is to compare self-reported time (by questionnaire) and objectively measured time (by accelerometer) spent on physical activity at moderate (MPA) and vigorous intensity (VPA) in subgroups of age, gender, education and weight status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
199
5
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(229 citation statements)
references
References 33 publications
(27 reference statements)
16
199
5
6
Order By: Relevance
“…Objective measures of energy expenditure (for example, accelerometer or doubly labeled water, a technique, which uses the naturally occurring stable isotopes of water to assess energy expenditure) or energy intake (for example, direct observation) are more accurate and less subject to reporting bias as compared with self-reports based on participant recall. 73,74 Only 1 study used an objective measure of energy intake 51 while 11 studies used objective measures of energy expenditure. Nevertheless, there is a paucity of studies using objective measures across multiple nationally representative samples, especially for physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Objective measures of energy expenditure (for example, accelerometer or doubly labeled water, a technique, which uses the naturally occurring stable isotopes of water to assess energy expenditure) or energy intake (for example, direct observation) are more accurate and less subject to reporting bias as compared with self-reports based on participant recall. 73,74 Only 1 study used an objective measure of energy intake 51 while 11 studies used objective measures of energy expenditure. Nevertheless, there is a paucity of studies using objective measures across multiple nationally representative samples, especially for physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, responses could have been biased by social desirability or participants' tendency to report practicing PA more than they really do. Regarding this later issue, recent studies have shown that individuals indeed tend to indicate that they have engaged in more PA when asked to self-report than when their behavior is evaluated with an objective measure, such as an accelerometer (Dyrstad, Hansen, Holme, & Anderssen, 2014;Slootmaker, Schuit, Chinapaw, Seidell, & van Mechelen, 2009;Tucker, Welk, & Beyler, 2011). Future research should thus consider supplying self-reported measures of PA practice with objective tools, such as accelerometers.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…The main drawback of self-reported PA is that participants tend to overestimate their PA amounts and intensity and often as a consequence are misclassified as meeting recommended PA guidelines [15,16,17,18,19]. Considering this limitation, some studies have shown moderate agreement between subjective and objective measurement methods of PA [20,21,22,23]. Furthermore, this study was not concerned with the assessment of participant PA amounts.…”
Section: Discussionmentioning
confidence: 99%